Negative electrode, preparation method thereof and battery
By using aldehyde polyethylene glycol aldehyde group and hydroxyl-containing aqueous binder in the inner and outer layers of the negative electrode sheet, the problems of black spots and purple spots caused by excessive infiltration time are solved, and faster infiltration effect and better battery electrical performance are achieved.
Patent Information
- Application Number
- CN202411765436.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-03
AI Technical Summary
In the prior art, due to the long infiltration time, more black spots and purple spots appear on the surface of the negative electrode sheet, which affects the performance of the battery cell capacity and the overall electrical performance.
The negative electrode with a bilayer structure is adopted, and the inner and outer layers contain aldehyde polyethylene glycol aldehyde groups as liquid absorbents, and are combined with an aqueous binder containing hydroxyl groups to improve wetting properties through polymerization reaction.
It effectively improves the wetting effect and speed of the negative electrode sheet, improves the overall electrical performance of the battery, and reduces the number of black spots, making it suitable for industrial production.
Smart Images

Figure BDA0005170932480000111 
Figure BDA0005170932480000121 
Figure BDA0005170932480000122
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy batteries, and in particular to a negative electrode and a preparation method thereof, and a battery. Background Art
[0002] Compared with traditional processes, the double-layer coating technology of battery pole pieces can effectively improve battery rate, energy density and cycle life. The existing double-layer coating technology improves the high and low temperature, rate cycle, DCR, storage and other electrical properties of the battery cell by adjusting the binder layered structure, the conductive agent layered structure, the porosity layered structure, the type of active particles, the particle size layered structure and the thickness control of the two-layer film area. Since the active material in the double-layer coating technology is two layers, it also brings problems such as the difficulty of pole piece wettability. When the battery was disassembled using the normal infiltration time, it was found that there were more black spots and purple spots on the surface of the negative pole piece. At the same time, the trace water and side reaction acid substances in the battery are also related to the appearance of black spots and purple spots, which comprehensively affect the capacity of the battery cell and the overall electrical performance.
[0003] Therefore, how to improve the wetting rate in double-layer coating is an urgent problem to be solved in this field. Summary of the invention
[0004] In view of this, the present invention is committed to providing a negative electrode and a preparation method thereof and a battery, so as to solve the problem in the prior art that a large number of black spots and purple spots appear on the surface of the negative electrode plate due to too long infiltration time.
[0005] In order to solve the above technical problems, this application is implemented as follows:
[0006] A first aspect of the present invention provides a negative electrode, the negative electrode comprising a current collector, a first negative electrode active material layer disposed on a surface of the current collector, and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer;
[0007] Wherein, the first negative electrode active material layer comprises a first negative electrode active material, a first liquid absorbing agent and a first composite binder; the second negative electrode active material layer comprises a second negative electrode active material, a second liquid absorbing agent and a second composite binder;
[0008] The first liquid absorbent includes potassium formate and / or aldehyde-polyethylene glycol aldehyde, and the first composite binder includes a first aqueous binder containing hydroxyl groups; the second liquid absorbent includes potassium formate and / or aldehyde-polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing hydroxyl groups.
[0009] Optionally, in the first negative electrode active material layer, the mass ratio of the first negative electrode active material, the first liquid absorbing agent and the first composite binder is (70-90): (0.5-1.5): (1.0-2.5); preferably (75-85): (0.7-1.2): (1.2-2.4); and / or, in the second negative electrode active material layer, the mass ratio of the second negative electrode active material, the second liquid absorbing agent and the second composite binder is (80-98): (0.2-0.6): (0.5-1.5); preferably (85-95): (0.3-0.5): (0.6-1.3); preferably, the masses of the first liquid absorbing agent and the second liquid absorbing agent satisfy the following formula:
[0010] x=-5y 2 +6.5y-0.8,
[0011] Wherein, x represents the mass of the first absorbent, and y represents the mass of the second absorbent.
[0012] Optionally, the mass density of the first negative electrode active material in the first negative electrode active material layer is 60 to 100 mg / cm 3 , preferably 70 to 90 mg / cm 3 ; Optionally, the first negative electrode active material is selected from at least one of natural graphite, artificial graphite, soft carbon and hard carbon; and / or, the mass density of the second negative electrode active material in the second negative electrode active material layer is 40 to 90 mg / cm 3 , preferably 50 to 80 mg / cm 3 ; Optionally, the second negative electrode active material is selected from at least one of natural graphite, artificial graphite, soft carbon and hard carbon.
[0013] Optionally, the first composite binder also includes styrene-butadiene rubber; optionally, the mass ratio of the first hydroxyl-containing aqueous binder to the styrene-butadiene rubber is (0.5-3): (0.1-0.5), preferably (1-2): (0.2-0.4); optionally, the first hydroxyl-containing aqueous binder is selected from at least one of cellulose acetate, hydroxyethyl cellulose, methyl cellulose, polyvinyl alcohol and polyacrylamide; and / or, the second composite binder also includes styrene-butadiene rubber; optionally, the mass ratio of the second hydroxyl-containing aqueous binder to the styrene-butadiene rubber is (0.3-1.2): (0.1-0.5), preferably (0.5-1): (0.1-0.3); optionally, the second hydroxyl-containing aqueous binder is selected from at least one of cellulose acetate, hydroxyethyl cellulose, methyl cellulose, polyvinyl alcohol and polyacrylamide.
[0014] Optionally, the first negative electrode active material layer also includes a first conductive agent; optionally, in the first negative electrode active material layer, the mass ratio of the first negative electrode active material to the first conductive agent is (70-90): (1.5-4.5), preferably (75-85): (2-4); optionally, the first conductive agent is selected from at least one of graphite, carbon black, graphene, conductive carbon black and acetylene black; and / or, the second negative electrode active material layer also includes a second conductive agent; optionally, in the second negative electrode active material layer, the mass ratio of the first negative electrode active material to the second conductive agent is (80-98): (3.2-5.5); preferably (85-95): (3-5); optionally, the second conductive agent is selected from at least one of graphite, carbon black, graphene, conductive carbon black and acetylene black.
[0015] Optionally, the thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:2-4, preferably 1:2-3; optionally, the thickness of the first negative electrode active material layer is 90-150 μm, preferably 100-120 μm; optionally, the thickness of the second negative electrode active material layer is 50-90 μm, preferably 65-75 μm.
[0016] A second aspect of the present invention provides a method for preparing a negative electrode, the method comprising the following steps:
[0017] S1, coating the inner layer slurry on the surface of the current collector and performing a first drying process to obtain a current collector provided with a first negative electrode active material layer;
[0018] S2, coating the outer layer slurry on the surface of the current collector provided with the first negative electrode active material layer and performing a second drying process;
[0019] Wherein, the inner layer slurry comprises a first negative electrode active material, a first liquid absorbing agent and a first composite binder; wherein, the first liquid absorbing agent comprises potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the first composite binder comprises a first aqueous binder containing a hydroxyl group;
[0020] The outer layer slurry includes a second negative electrode active material, a second liquid absorbing agent and a second composite binder; wherein the second liquid absorbing agent includes potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing a hydroxyl group.
[0021] Optionally, the configuration step of the inner layer slurry includes: a first mixing of a first negative electrode active material, a first conductive agent, a first composite binder and a first solvent to obtain a first material; adding a first liquid absorbent to the first material and performing a second mixing; wherein the first liquid absorbent includes potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the first composite binder includes a first aqueous binder containing hydroxyl groups; optionally, the first solvent is water; and / or, the configuration step of the outer layer slurry includes: a third mixing of a second negative electrode active material, a second conductive agent, a second composite binder and a second solvent to obtain a second material; adding a second liquid absorbent to the second material and performing a third mixing; wherein the second liquid absorbent includes potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing hydroxyl groups; optionally, the second solvent is water.
[0022] Optionally, the inner layer slurry comprises: 75 to 80 parts by mass of the first negative electrode active material, 2 to 4 parts by mass of the first conductive agent, 1.2 to 2.4 parts by mass of the first composite binder, 0.7 to 1.2 parts by mass of the first liquid absorbent and 20 to 30 parts by mass of the first solvent; and / or, the outer layer slurry comprises: 85 to 95 parts by mass of the second negative electrode active material, 3 to 5 parts by mass of the second conductive agent, 0.6 to 1.3 parts by mass of the second composite binder, 0.3 to 0.5 parts by mass of the second liquid absorbent and 35 to 45 parts by mass of the second solvent.
[0023] A third aspect of the present invention provides a battery, comprising the above-mentioned negative electrode and / or the negative electrode prepared according to the above-mentioned method.
[0024] Through the above technical solution, the beneficial technical effects of the present invention are:
[0025] (1) The negative electrode in the present invention includes a first negative electrode active material layer (inner layer) disposed on the surface of the current collector and a second negative electrode active material layer (outer layer) disposed on the surface of the first negative electrode active material layer away from the current collector. The first negative electrode active material layer includes a first liquid absorbent and a first aqueous binder containing hydroxyl groups; the second negative electrode active material layer includes a second liquid absorbent and a second aqueous binder containing hydroxyl groups; the first liquid absorbent and the second liquid absorbent respectively contain aldehyde groups, and the aldehyde groups of the liquid absorbent polymerize with the hydroxyl groups in the binder, so that the liquid absorbent can be dispersed more evenly, which is beneficial to the rapid liquid absorption of the entire electrode.
[0026] (2) The negative electrode sheet of the present invention improves the wetting effect and speed while improving the overall electrical performance of the battery. The negative electrode sheet of the present invention has a simple preparation process and is easy to realize industrial production.
[0027] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0028] The present invention discloses a negative electrode and a method for preparing the same and a battery. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0029] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] In order to solve the problem in the prior art that a large number of black spots and purple spots appear on the surface of the negative electrode sheet due to the long infiltration time, the present invention adopts the following technical solution:
[0035] A first aspect of the present invention provides a negative electrode, the negative electrode comprising a current collector, a first negative electrode active material layer disposed on a surface of the current collector, and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer;
[0036] Wherein, the first negative electrode active material layer comprises a first negative electrode active material, a first liquid absorbing agent and a first composite binder; the second negative electrode active material layer comprises a second negative electrode active material, a second liquid absorbing agent and a second composite binder;
[0037] The first liquid absorbent includes potassium formate and / or aldehyde-polyethylene glycol aldehyde, and the first composite binder includes a first aqueous binder containing hydroxyl groups; the second liquid absorbent includes potassium formate and / or aldehyde-polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing hydroxyl groups.
[0038] The negative electrode in the present invention comprises a first negative electrode active material layer (inner layer) arranged on the surface of the current collector and a second negative electrode active material layer (outer layer) arranged on the surface of the first negative electrode active material layer away from the current collector. The present invention adds an aldehyde-containing liquid absorbent and a hydroxyl-containing aqueous binder to the inner and outer layers of the negative electrode respectively. The aldehyde group of the liquid absorbent polymerizes with the hydroxyl group in the aqueous binder to make the liquid absorbent more evenly dispersed, which is beneficial to the rapid liquid absorption of the entire electrode, can improve the wetting effect and speed, and is beneficial to improving the overall electrical performance of the battery.
[0039] In a preferred embodiment of the present invention, the first liquid absorbent and the second liquid absorbent respectively include potassium formate. In this embodiment, potassium formate can react with water in an exothermic reaction, effectively remove harmful trace water inside the battery, and improve the overall electrochemical performance of the battery. In addition, an exothermic reaction also occurs, and the battery can be used in a low-temperature environment (for example, -30°C), and the temperature of the battery cell is increased so that the battery cell can be used normally in a low-temperature environment, which can effectively improve the defect of lithium iron phosphate batteries with poor performance at low temperatures. In addition, potassium formate can also react with acid, and can remove acidic substances generated by side reactions of the electrolyte, which is beneficial to further improve battery performance; the liquid absorbent and the binder are effectively combined through a polymerization reaction, which improves wettability while greatly optimizing battery performance.
[0040] According to the present invention, since the liquid absorbent in the second negative electrode active material layer (outer layer) can directly contact the electrolyte and absorb liquid more quickly, the amount of the liquid absorbent added in the first negative electrode active material layer (inner layer) is higher than that in the second negative electrode active material layer (outer layer) to facilitate rapid wetting of the electrode sheet. Exemplarily, in the first negative electrode active material layer, the mass ratio of the first negative electrode active material, the first liquid absorbent and the first composite binder can be (70-90): (0.5-1.5): (1.0-2.5); in the second negative electrode active material layer, the mass ratio of the second negative electrode active material, the second liquid absorbent and the second composite binder can be (80-98): (0.2-0.6): (0.5-1.5).
[0041] Preferably, in the first negative electrode active material layer, the mass ratio of the first negative electrode active material, the first liquid absorbing agent and the first composite binder can be (75-85): (0.7-1.2): (1.2-2.4); in the second negative electrode active material layer, the mass ratio of the second negative electrode active material, the second liquid absorbing agent and the second composite binder can be (85-95): (0.3-0.5): (0.6-1.3).
[0042] In a preferred embodiment of the present invention, the masses of the first absorbent and the second absorbent satisfy the following formula:
[0043] x=-5y 2 +6.5y-0.8,
[0044] Wherein, x represents the mass of the first absorbent, and y represents the mass of the second absorbent. In this embodiment, the mass of the first absorbent first increases and then decreases with the mass of the second absorbent, thereby ensuring the rapid wetting of the electrode sheet; when the two layers of absorbent reach a certain amount, the wetting speed and the amount of addition are not significantly changed when the amount of absorbent is increased, and the trend of reducing the wetting time is weakened.
[0045] According to the present invention, the mass density of the first negative electrode active material can ensure the lithium ion diffusion effect in the inner layer while ensuring the lithium insertion effect in the outer layer. In the present invention, the mass density of the first negative electrode active material in the first negative electrode active material layer can be 60-100 mg / cm 3 For example, the mass density of the first negative electrode active material may be 60 mg / cm 3 、70mg / cm 3 、80mg / cm 3 、90mg / cm 3 and 100mg / cm 3Any value in or any value in the range formed by any two of the above values. In the present invention, if the mass density of the first negative electrode active material is too high, it can provide more lithium insertion sites, which may cause the second negative electrode active material to become less and be unfavorable for the diffusion of lithium ions in the inner layer; if the mass density of the first negative electrode active material is too low, it may cause too few lithium insertion sites in the outer layer, which is not conducive to fast charging. Preferably, the mass density of the first negative electrode active material can be 70-90 mg / cm 3 .
[0046] Illustratively, the first negative electrode active material may be selected from at least one of natural graphite, artificial graphite, soft carbon, and hard carbon.
[0047] According to the present invention, the mass density of the second negative electrode active material can ensure the lithium ion diffusion effect in the inner layer while ensuring the lithium insertion effect in the outer layer. In the present invention, the mass density of the second negative electrode active material in the second negative electrode active material layer can be 40 to 90 mg / cm 3 For example, the mass density of the second negative electrode active material may be 40 mg / cm 3 、50mg / cm 3 、60mg / cm 3 、70mg / cm 3 、80mg / cm 3 and 90mg / cm 3 Any value in or any value in the range of values formed by any two of the above values. In the present invention, if the mass density of the second negative electrode active material is too high, it may lead to too few lithium insertion sites in the outer layer, which is not conducive to fast charging; if the mass density of the second negative electrode active material is too low, it may lead to the second negative electrode active material becoming less, which is not conducive to the diffusion of lithium ions in the inner layer. Preferably, the mass density of the second negative electrode active material can be 50-80 mg / cm 3 .
[0048] Illustratively, the second negative electrode active material may be selected from at least one of natural graphite, artificial graphite, soft carbon, and hard carbon.
[0049] According to the present invention, the first composite binder may also include styrene-butadiene rubber; optionally, the mass ratio of the first hydroxyl-containing aqueous binder to the styrene-butadiene rubber may be (0.5-3): (0.1-0.5), and the suitable ratio of the first hydroxyl-containing aqueous binder to the styrene-butadiene rubber in the present invention can improve the liquid absorption rate of the first liquid absorbing agent in the first negative electrode active material layer while ensuring the bonding effect. Preferably, the mass ratio of the first hydroxyl-containing aqueous binder to the styrene-butadiene rubber may be (1-2): (0.2-0.4).
[0050] Illustratively, the first hydroxyl-containing aqueous binder may be selected from at least one of cellulose acetate, hydroxyethyl cellulose, methyl cellulose, polyvinyl alcohol, and polyacrylamide.
[0051] Exemplarily, the second composite binder further includes styrene-butadiene rubber.
[0052] According to the present invention, the mass ratio of the second hydroxyl-containing aqueous binder to the styrene-butadiene rubber can be (0.3-1.2): (0.1-0.5). The suitable ratio of the second hydroxyl-containing aqueous binder to the styrene-butadiene rubber in the present invention can improve the liquid absorption rate of the second liquid absorbing agent in the second negative electrode active material layer while ensuring the bonding effect. Preferably, the mass ratio of the second hydroxyl-containing aqueous binder to the styrene-butadiene rubber can be (0.5-1): (0.1-0.3).
[0053] Illustratively, the second hydroxyl-containing aqueous binder may be selected from at least one of cellulose acetate, hydroxyethyl cellulose, methyl cellulose, polyvinyl alcohol and polyacrylamide.
[0054] According to the present invention, the first negative electrode active material layer may further include a first conductive agent; optionally, in the first negative electrode active material layer, the mass ratio of the first negative electrode active material to the first conductive agent is (70-90): (1.5-4.5), preferably (75-85): (2-4).
[0055] Exemplarily, the first conductive agent may be selected from at least one of graphite, carbon black, graphene, conductive carbon black and acetylene black.
[0056] According to the present invention, the second negative electrode active material layer may further include a second conductive agent; optionally, the mass ratio of the second negative electrode active material layer to the second conductive agent may be (80-98):(3.2-5.5); preferably (85-95):(3-5).
[0057] Exemplarily, the second conductive agent may be selected from at least one of graphite, carbon black, graphene, conductive carbon black and acetylene black.
[0058] According to the present invention, a suitable thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer is conducive to improving the overall electrical performance of the battery. In the present invention, the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer can be 1:2-4. For example, the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer can be any value of 1:2, 1:2.5, 1:3, 1:3.5 and 1:4 or any value within the range of any two of the above values. In the present invention, if the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer is too high, that is, the thickness of the first negative electrode active material layer is relatively large, it may take more time for lithium ions to be embedded in the inner layer; if the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer is too low, that is, the thickness of the second negative electrode active material layer is relatively large, it may be unfavorable for the rapid embedding of lithium ions. Preferably, the thickness ratio of the first negative electrode active material layer and the second negative electrode active material layer can be 1:2-3.
[0059] According to the present invention, the thickness of the first negative electrode active material layer may be 90 to 150 μm. Exemplarily, the thickness of the first negative electrode active material layer may be any value among 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm and 150 μm, or any value within the range of any two of the above values. Preferably, the thickness of the first negative electrode active material layer may be 100 to 120 μm.
[0060] According to the present invention, the thickness of the second negative electrode active material layer may be 50 to 90 μm. Exemplarily, the thickness of the second negative electrode active material layer may be any value among 50 μm, 60 μm, 70 μm, 80 μm and 90 μm, or any value within the range of any two of the above values. Preferably, the thickness of the second negative electrode active material layer may be 65 to 75 μm.
[0061] A second aspect of the present invention provides a method for preparing a negative electrode, the method comprising the following steps:
[0062] S1, coating the inner layer slurry on the surface of the current collector and performing a first drying process to obtain a current collector provided with a first negative electrode active material layer;
[0063] S2, coating the outer layer slurry on the surface of the current collector provided with the first negative electrode active material layer and performing a second drying process;
[0064] Wherein, the inner layer slurry comprises a first negative electrode active material, a first liquid absorbing agent and a first composite binder; wherein, the first liquid absorbing agent comprises potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the first composite binder comprises a first aqueous binder containing a hydroxyl group;
[0065] The outer layer slurry includes a second negative electrode active material, a second liquid absorbing agent and a second composite binder; wherein the second liquid absorbing agent includes potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing a hydroxyl group.
[0066] In one embodiment of the present invention, the inner layer slurry configuration step may include: first mixing a first negative electrode active material, a first conductive agent, a first composite binder and a first solvent to obtain a first material; adding a first liquid absorbing agent to the first material and performing a second mixing.
[0067] Exemplarily, the first liquid absorbing agent may include potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the first composite binder may include a first aqueous binder containing a hydroxyl group.
[0068] Illustratively, the first solvent may be water.
[0069] In another embodiment of the present invention, the step of configuring the outer layer slurry may include: performing a third mixing of a second negative electrode active material, a second conductive agent, a second composite binder and a second solvent to obtain a second material; adding a second liquid absorbing agent to the second material and performing a third mixing.
[0070] Exemplarily, the second liquid absorbing agent may include potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the second composite binder may include a second aqueous binder containing a hydroxyl group.
[0071] Illustratively, the second solvent may be water.
[0072] According to the present invention, the inner layer slurry may include: 75-80 parts by mass of the first negative electrode active material, 2-4 parts by mass of the first conductive agent, 1.2-2.4 parts by mass of the first composite binder, 0.7-1.2 parts by mass of the first liquid absorbing agent and 20-30 parts by mass of the first solvent.
[0073] According to the present invention, the outer layer slurry may include: 85-95 parts by mass of the second negative electrode active material, 3-5 parts by mass of the second conductive agent, 0.6-1.3 parts by mass of the second composite binder, 0.3-0.5 parts by mass of the second liquid absorbing agent and 35-45 parts by mass of the second solvent.
[0074] A third aspect of the present invention provides a battery, comprising the above-mentioned negative electrode and / or the negative electrode prepared according to the above-mentioned method.
[0075] The present invention is further described in detail by way of examples. The raw materials used in the examples can be obtained through commercial sources.
[0076] Example 1
[0077] (1) Preparation of inner and outer slurry: 75 parts of natural graphite, 2 parts of conductive carbon black (SP), 1 part of cellulose acetate, 0.2 parts of styrene-butadiene rubber and 20 parts of deionized water were stirred for 120 minutes to obtain a first material; 0.7 parts of potassium formate were added to the first material and stirred for 30 minutes to obtain an inner slurry. 85 parts of artificial graphite, 3 parts of SP, 0.5 parts of cellulose acetate, 0.1 parts of styrene-butadiene rubber and 35 parts of deionized water were stirred for 120 minutes to obtain a second material; 0.3 parts of potassium formate were added to the second material and stirred for 30 minutes to obtain an outer slurry.
[0078] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0079] (3) Preparation of positive electrode sheets: Lithium iron phosphate, conductive carbon black (SP), binder polyvinylidene fluoride (PVDF) were mixed in a ratio of 95:3:2 with an appropriate amount of N-methylpyrrolidone (NMP) to prepare a positive electrode slurry, which was coated on aluminum foil, dried by air at 100°C, and cold pressed and cut into positive electrode sheets.
[0080] (4) Battery preparation: The positive electrode sheet, separator, and negative electrode sheet are wound into a core, wherein the separator completely covers the positive electrode sheet and the negative electrode sheet. The core is then placed in a metal shell or wrapped with an aluminum-plastic film and then injected with electrolyte. Finally, a lithium iron phosphate battery is made through processes such as standing, formation, and capacity separation.
[0081] Example 2
[0082] (1) Preparation of inner and outer slurry: 80 parts of natural graphite, 3 parts of conductive carbon black (SP), 1.5 parts of cellulose acetate, 0.3 parts of styrene butadiene rubber and 25 parts of deionized water were stirred for 120 minutes to obtain a first material; 1 part of potassium formate was added to the first material and stirred for 30 minutes to obtain an inner slurry. 90 parts of artificial graphite, 4 parts of SP, 0.7 parts of cellulose acetate, 0.2 parts of styrene butadiene rubber and 40 parts of deionized water were stirred for 120 minutes to obtain a second material; 0.4 parts of potassium formate was added to the second material and stirred for 30 minutes to obtain an outer slurry.
[0083] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0084] The preparation method of the positive electrode sheet and the preparation method of the battery in this embodiment are the same as those in Example 1.
[0085] Example 3
[0086] (1) Preparation of inner and outer slurry: 85 parts of natural graphite, 4 parts of conductive carbon black (SP), 2 parts of cellulose acetate, 0.4 parts of styrene-butadiene rubber and 30 parts of deionized water were stirred for 120 minutes to obtain a first material; 1.2 parts of potassium formate were added to the first material and stirred for 30 minutes to obtain an inner slurry. 95 parts of artificial graphite, 5 parts of SP, 1 part of cellulose acetate, 0.3 parts of styrene-butadiene rubber and 30 parts of deionized water were stirred for 120 minutes to obtain a second material; 0.5 parts of potassium formate were added to the second material and stirred for 30 minutes to obtain an outer slurry.
[0087] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0088] The preparation method of the positive electrode sheet and the preparation method of the battery in this embodiment are the same as those in Example 1.
[0089] Example 4
[0090] (1) Preparation of inner and outer slurry: 85 parts of natural graphite, 4 parts of conductive carbon black (SP), 2 parts of cellulose acetate, 0.4 parts of styrene-butadiene rubber and 30 parts of deionized water were stirred for 120 minutes to obtain a first material; 1.2 parts of aldehyde-based polyethylene glycol were added to the first material and stirred for 30 minutes to obtain an inner slurry. 95 parts of artificial graphite, 5 parts of SP, 1 part of cellulose acetate, 0.3 parts of styrene-butadiene rubber and 45 parts of deionized water were stirred for 120 minutes to obtain a second material; 0.5 parts of aldehyde-based polyethylene glycol were added to the second material and stirred for 30 minutes to obtain an outer slurry.
[0091] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0092] The preparation method of the positive electrode sheet and the preparation method of the battery in this embodiment are the same as those in Example 1.
[0093] Comparative Example 1
[0094] (1) Preparation of inner layer slurry and outer layer slurry: 75 parts of natural graphite, 2 parts of conductive carbon black (SP), 1 part of cellulose acetate, 0.2 parts of styrene butadiene rubber and 20 parts of deionized water were stirred for 120 minutes to obtain the inner layer slurry. 85 parts of artificial graphite, 3 parts of SP, 0.5 parts of cellulose acetate, 0.1 parts of styrene butadiene rubber and 35 parts of deionized water were stirred for 120 minutes to obtain the second material; 0.3 parts of potassium formate was added to the second material and stirred for 30 minutes to obtain the outer layer slurry.
[0095] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0096] The preparation method of the positive electrode sheet and the preparation method of the battery in this comparative example are the same as those in Example 1.
[0097] Comparative Example 2
[0098] (1) Preparation of inner layer slurry and outer layer slurry: 75 parts of natural graphite, 2 parts of conductive carbon black (SP), 1 part of cellulose acetate, 0.2 parts of styrene butadiene rubber and 20 parts of deionized water were stirred for 120 minutes to obtain a first material; 0.7 parts of potassium formate were added to the first material and stirred for 30 minutes to obtain an inner layer slurry. 85 parts of artificial graphite, 3 parts of SP, 0.5 parts of cellulose acetate, 0.1 parts of styrene butadiene rubber and 35 parts of deionized water were stirred for 120 minutes to obtain an outer layer slurry.
[0099] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0100] The preparation method of the positive electrode sheet and the preparation method of the battery in this comparative example are the same as those in Example 1.
[0101] Comparative Example 3
[0102] (1) Preparation of inner layer slurry and outer layer slurry: 75 parts of natural graphite, 2 parts of conductive carbon black (SP), 1 part of cellulose acetate, 0.2 parts of styrene butadiene rubber and 20 parts of deionized water were stirred for 120 minutes to obtain inner layer slurry. 85 parts of artificial graphite, 3 parts of SP, 0.5 parts of cellulose acetate, 0.1 parts of styrene butadiene rubber and 35 parts of deionized water were stirred for 120 minutes to obtain outer layer slurry.
[0103] (2) Preparation of negative electrode sheets: the inner layer slurry is coated on the surface of an aluminum foil and subjected to a first drying treatment at a drying temperature of 90°C to obtain an aluminum foil provided with a first negative electrode active material layer, wherein the thickness of the first negative electrode active material layer is 100 μm; the outer layer slurry is coated on the surface of the aluminum foil provided with the first negative electrode active material layer and subjected to a second drying treatment at a drying temperature of 90°C to obtain a negative electrode sheet, wherein the thickness of the second negative electrode active material layer is 80 μm.
[0104] The preparation method of the positive electrode sheet and the preparation method of the battery in this comparative example are the same as those in Example 1.
[0105] The composition analysis of the inner layer slurry and the outer layer slurry in Examples 1 to 4 and Comparative Examples 1 to 3 is shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] Test Example 1
[0110] The batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to cycle tests and battery capacity post-interface confirmation tests. The test results are shown in Table 2.
[0111] The cycle test method includes: charging the battery at 0.5C constant current and constant voltage to 3.65V at 25°C, with a cutoff condition of 0.05C; discharging at 0.5C to 2.5V after standing for 60 minutes, continuing the above process until the capacity decays to 80% of the initial test capacity, and recording the number of cycles.
[0112] The method for the battery capacity post-interface confirmation test includes: after the battery capacity is completed, the battery is fully charged at 0.5C to 3.65V, and after full charging, the battery is disassembled to confirm the interface.
[0113] Low temperature performance test: At -30℃, charge the battery at 0.05C constant current and constant voltage to 4.0V, with a cut-off condition of 0.05C; after standing for 60 minutes, discharge at 0.3C to 1.5V, and continue the above process until the capacity decays to 80% of the initial test capacity, and record the number of cycles.
[0114] Table 2
[0115]
[0116] It can be seen from Table 2 that in the embodiments of the present invention, an aldehyde-containing liquid absorbent and a hydroxyl-containing aqueous binder are respectively added to the inner and outer layers of the negative electrode. The use of the aldehyde-containing liquid absorbent and the hydroxyl-containing aqueous binder can effectively reduce the number of black spots and increase the number of battery cycles.
[0117] Specifically, it can be seen from the data of Examples 1 to 3 that by appropriately increasing the content of the liquid absorbent in the inner and outer layers, the number of cycles of the cycle test is greater than 3200, showing good cycle performance; the number of cycles of the low temperature performance test is greater than 1500, showing good low temperature performance; and the number of black spots on the negative interface is significantly reduced. It can be seen from the data of Example 1 and Comparative Example 1 that when only the liquid absorbent is added to the outer layer additive, the number of cycles of the cycle test is reduced to 2467, the number of cycles of the low temperature performance test is reduced to 1428, and the number of black spots on the negative interface is reduced to 6; it can be seen from the data of Example 1 and Comparative Example 2 that when only the liquid absorbent is added to the inner layer additive, the number of cycles of the cycle test is reduced to 2619, the number of cycles of the low temperature performance test is reduced to 1443, and the number of black spots on the negative interface is reduced to 2; that is, the present invention absorbs liquid in both the inner and outer layers of the negative electrode, which can effectively reduce the number of black spots and improve the number of cycles and low temperature performance of the battery.
[0118] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A negative electrode, characterized in that: The negative electrode comprises a current collector, a first negative electrode active material layer disposed on a surface of the current collector, and a second negative electrode active material layer disposed on a surface of the first negative electrode active material layer; Wherein, the first negative electrode active material layer comprises a first negative electrode active material, a first liquid absorbing agent and a first composite binder; the second negative electrode active material layer comprises a second negative electrode active material, a second liquid absorbing agent and a second composite binder; The first liquid absorbent includes potassium formate and / or aldehyde-polyethylene glycol aldehyde, and the first composite binder includes a first aqueous binder containing hydroxyl groups; the second liquid absorbent includes potassium formate and / or aldehyde-polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing hydroxyl groups.
2. The negative electrode according to claim 1, characterized in that In the first negative electrode active material layer, the mass ratio of the first negative electrode active material, the first liquid absorbing agent and the first composite binder is (70-90): (0.5-1.5): (1.0-2.5); preferably (75-85): (0.7-1.2): (1.2-2.4); and / or, In the second negative electrode active material layer, the mass ratio of the second negative electrode active material, the second liquid absorbing agent and the second composite binder is (80-98): (0.2-0.6): (0.5-1.5); preferably (85-95): (0.3-0.5): (0.6-1.3); Preferably, the masses of the first absorbent and the second absorbent satisfy the following formula: x=-5y 2 +6.5y-0.8, Wherein, x represents the mass of the first absorbent, and y represents the mass of the second absorbent.
3. The negative electrode according to claim 1 or 2, characterized in that The mass density of the first negative electrode active material in the first negative electrode active material layer is 60 to 100 mg / cm 3 , preferably 70 to 90 mg / cm 3 ; Optionally, the first negative electrode active material is selected from at least one of natural graphite, artificial graphite, soft carbon and hard carbon; and / or, The mass density of the second negative electrode active material in the second negative electrode active material layer is 40 to 90 mg / cm 3 , preferably 50 to 80 mg / cm 3 ; Optionally, the second negative electrode active material is selected from at least one of natural graphite, artificial graphite, soft carbon and hard carbon.
4. The negative electrode according to claim 1, characterized in that The first composite adhesive further includes styrene-butadiene rubber; Optionally, the mass ratio of the first hydroxyl-containing aqueous binder to the styrene-butadiene rubber is (0.5-3): (0.1-0.5), preferably (1-2): (0.2-0.4); Optionally, the first hydroxyl-containing aqueous binder is selected from at least one of cellulose acetate, hydroxyethyl cellulose, methyl cellulose, polyvinyl alcohol and polyacrylamide; and / or, The second composite binder also includes styrene-butadiene rubber; Optionally, the mass ratio of the second hydroxyl-containing aqueous binder to the styrene-butadiene rubber is (0.3-1.2):(0.1-0.5), preferably (0.5-1):(0.1-0.3); Optionally, the second hydroxyl-containing aqueous binder is selected from at least one of cellulose acetate, hydroxyethyl cellulose, methyl cellulose, polyvinyl alcohol and polyacrylamide.
5. The negative electrode according to claim 1, characterized in that The first negative electrode active material layer further includes a first conductive agent; Optionally, in the first negative electrode active material layer, the mass ratio of the first negative electrode active material to the first conductive agent is (70-90): (1.5-4.5), preferably (75-85): (2-4); Optionally, the first conductive agent is selected from at least one of graphite, carbon black, graphene, conductive carbon black and acetylene black; and / or, The second negative electrode active material layer further includes a second conductive agent; Optionally, the mass ratio of the second negative electrode active material layer to the second conductive agent is (80-98): (3.2-5.5); preferably (85-95): (3-5); Optionally, the second conductive agent is selected from at least one of graphite, carbon black, graphene, conductive carbon black and acetylene black.
6. The negative electrode according to claim 1, characterized in that The thickness ratio of the first negative electrode active material layer to the second negative electrode active material layer is 1:(2-4), preferably 1:(2-3); Optionally, the thickness of the first negative electrode active material layer is 90 to 150 μm, preferably 100 to 120 μm; Optionally, the thickness of the second negative electrode active material layer is 50 to 90 μm, preferably 65 to 75 μm.
7. A method for preparing the negative electrode according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: S1, coating the inner layer slurry on the surface of the current collector and performing a first drying process to obtain a current collector provided with a first negative electrode active material layer; S2, coating the outer layer slurry on the surface of the current collector provided with the first negative electrode active material layer and performing a second drying process; Wherein, the inner layer slurry comprises a first negative electrode active material, a first liquid absorbing agent and a first composite binder; wherein, the first liquid absorbing agent comprises potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the first composite binder comprises a first aqueous binder containing a hydroxyl group; The outer layer slurry includes a second negative electrode active material, a second liquid absorbing agent and a second composite binder; wherein the second liquid absorbing agent includes potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing a hydroxyl group.
8. The preparation method according to claim 7, characterized in that: The inner layer slurry configuration step includes: first mixing a first negative electrode active material, a first conductive agent, a first composite binder and a first solvent to obtain a first material; adding a first liquid absorbing agent to the first material and performing a second mixing; wherein the first liquid absorbing agent includes potassium formate and / or aldehyde-based polyethylene glycol aldehyde, and the first composite binder includes a first aqueous binder containing a hydroxyl group; optionally, the first solvent is water; and / or, The steps of configuring the outer layer slurry include: performing a third mixing of a second negative electrode active material, a second conductive agent, a second composite binder and a second solvent to obtain a second material; adding a second liquid absorbing agent to the second material and performing a third mixing; wherein the second liquid absorbing agent includes potassium formate and / or aldehyde polyethylene glycol aldehyde, and the second composite binder includes a second aqueous binder containing a hydroxyl group; optionally, the second solvent is water.
9. The preparation method according to claim 8, characterized in that: The inner layer slurry comprises: 75 to 80 parts by mass of the first negative electrode active material, 2 to 4 parts by mass of the first conductive agent, 1.2 to 2.4 parts by mass of the first composite binder, 0.7 to 1.2 parts by mass of the first liquid absorbing agent, and 20 to 30 parts by mass of the first solvent; and / or, The outer layer slurry includes: 85-95 parts by mass of the second negative electrode active material, 3-5 parts by mass of the second conductive agent, 0.6-1.3 parts by mass of the second composite binder, 0.3-0.5 parts by mass of the second liquid absorbing agent and 35-45 parts by mass of the second solvent.
10. A battery, characterized in that: The battery comprises the negative electrode according to any one of claims 1 to 6 and / or the negative electrode prepared by the method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Preparation method for coating surfaces of electrodes with solid electrolyte complex liquid
CN105591105A
Fat-soluble polymer for positive plate, preparation method and positive plate
CN112500543A
Negative electrode material, preparation method of negative electrode slurry, and lithium secondary battery
CN114388792A
Preparation of graphite composite negative electrode material based on polycarboxylic acid potassium salt and application of composite negative electrode material to potassium ion battery
CN114614002A
Liquid injection method of aluminum plastic film soft package lithium iron phosphate battery
CN115101901A